Model Ibadah Keluarga Kristen: Implikasi Terhadap Pembentukan Karakter Remaja di Lingkungan Gereja - Herby Calvin Pascal Tiyow (JURNAL TRANSFORMASI: Jurnal Teologi dan Kepemimpinan, 2025)
This study aims to analyze the Christian family worship model and its implications on the character development of adolescents in the environment of the Gereja Yesus Hidup Sejati Cabang Diamond. The family, as the smallest unit in society, plays a crucial role in instilling moral and spiritual values in adolescents. Family worship serves as a means to introduce and internalize Christian values related to love, responsibility, and honesty. This research uses a qualitative approach with data analysis through in-depth interviews, participatory observations, and documentation. The data was analyzed using NVIVO software to identify key themes related to family worship practices and their impact on adolescent character development. The findings of the study indicate that family worship has a significant impact on shaping adolescent character, with the teaching of moral values contributing to the enhancement of responsibility, empathy, and family closeness. Additionally, the use of interactive methods such as discussions and multimedia tools can increase adolescents' interest in worship. The study recommends increasing the frequency of family worship and involving adolescents in planning worship to enhance their sense of responsibility.